2008
DOI: 10.4103/0255-0857.43566
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between biofilm production and multiple drug resistance in imipenem resistant clinical isolates ofAcinetobacter baumannii

Abstract: Microtitre plate method was found to be a more sensitive method for biofilm detection. This study demonstrates a high propensity among the clinical isolates of A. baumannii to form biofilm and a significant association of biofilms with multiple drug resistance. Presence of bla PER-1 appears to be more critical for cell adherence than for biofilm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 15 publications
6
35
2
Order By: Relevance
“…The absorbance values obtained with all 19 strains of MDR A. baumannii clearly differed from that with the negative control (A. baumannii 2508), and most of those strains showed biofilm formation (Fig. 1), which is consistent with earlier findings showing that MDR clinical isolates of A. baumannii form biofilms (53). Moreover, there is a significant association between biofilm formation and resistance to multiple drugs, including imipenem, cefotaxime, amikacin, and ciprofloxacin (53), although A. baumannii isolates from wound patients were also resistant to amikacin, ampicillin, aztreonam, ceftriaxone, ciprofloxacin, gentamicin, imipenem, tobramycin, and vancomycin (31).…”
Section: Effects Of Antibiotic Agents On Mdr a Baumannii Cells The 19supporting
confidence: 90%
“…The absorbance values obtained with all 19 strains of MDR A. baumannii clearly differed from that with the negative control (A. baumannii 2508), and most of those strains showed biofilm formation (Fig. 1), which is consistent with earlier findings showing that MDR clinical isolates of A. baumannii form biofilms (53). Moreover, there is a significant association between biofilm formation and resistance to multiple drugs, including imipenem, cefotaxime, amikacin, and ciprofloxacin (53), although A. baumannii isolates from wound patients were also resistant to amikacin, ampicillin, aztreonam, ceftriaxone, ciprofloxacin, gentamicin, imipenem, tobramycin, and vancomycin (31).…”
Section: Effects Of Antibiotic Agents On Mdr a Baumannii Cells The 19supporting
confidence: 90%
“…The prevalence of A. baumannii clone-22 during almost 5 years (the study period) suggested that the isolates of this clone could have factors that confer an advantage for its colonization and for biofilm production. Although the correlation between antibiotic resistance and biofilm production has already been reported for A. baumannii [7], we raised the question as to whether, in addition to the multidrug resistance exhibited by this clone, its production of biofilm could also account for its persistence in the hospital environment. To test this hypothesis, we measured the biofilm production and antimicrobial susceptibility in the 85 clinical isolates.…”
Section: Introductionmentioning
confidence: 88%
“…The emergence of clinical isolates with resistance to multiple antibiotics [7,8,9] greatly limits treatment options, especially if the organism is resistant to the carbapenem class of antibiotics [10]. In a previous report [11], we identified an increase in the isolation of multidrug-resistant A. baumannii in different wards of the Hospital Civil de Guadalajara (HCG-Mexico), a 1,000-bed, tertiary referral teaching hospital in western Mexico, with variable resistance to diverse antibiotics, including carbapenems.…”
Section: Introductionmentioning
confidence: 99%
“…V. anguillarum was procured from Central Institute of Brackish-water Aquaculture (CIBA), Chennai. The multidrug resistant bacteria Acinetobacter baumannii was obtained from Pondicherry Institute of Medical Sciences (PIMS), Pondicherry, India, and the strain was biochemically characterized (Prashanth et al, 2008). The pathogenic bacteria were cultured individually on tryptic soy broth at 37°C for 18 h, before inoculation for assay.…”
Section: Test Organismsmentioning
confidence: 99%